Preparation of low cost catalysts for proton exchange membrane fuel cell - Y. Pimpaya (2020)
© 2020 Institute of Physics Publishing. All rights reserved. Nitrogen-doped reduced graphene oxide (NG) with high nitrogen level was synthesized by a facile pyrolysis. NG has been getting attention because of its high catalytic activity toward the oxygen reduction reaction (ORR) and reduce cost. The synthesis of NG used graphene oxide (GO) and urea as a N-precursor were dissolved in ethanol. Then the mixture was evaporated by ultrasonic bath for 30 min. The mixture was slurry then was transferred to tube furnace and pyrolyzed at 300°C and 800°C (NG300 and NG800) with heating rate of 2.5 °C/min in N2 atmosphere for 30 min. The morphology and structure of nitrogen doped graphene oxide were investigated by Scanning Electron Microscopy (SEM) and X-ray photoemission spectroscopy (XPS). The XPS spectra of NG indicated that NG300 had the highest intensity of N1S peak among others. Mass of nitrogen of NG300 and NG800 were evaluated and had about 15.5%wt and 6.6%wt, respectively. Furthermore, N spectra at high-resolution was analysed and de-convoluted to three N chemical states of pyridinic-N, pyrrolic-N, and graphitic-N. The electrochemical properties of NG were determined by cyclic voltammetry (CV) and Linear sweep voltammetry (LSV). From the results shown that NG800 catalyst yielded highest electrochemical activity particularly for oxygen reduction reaction (ORR) over GO and NG300. Thus, N atoms doped into the graphene were responsible for the ORR catalytic activity resulting from doping N atoms and provided more density of active sites and conductivity. Moreover, NG can be applied as a supporting material for Non-precious metal group catalysts of fuel cell.